Integration of Islamic Economic Literacy and Hulondalo Local Values in Realizing the Financial Independence of Gorontalo’s Young Generation - Ansar Sahabi; Sri Apriyanti Husain; Sri Dewi Yusuf; Laras Ayu Sekarrini (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2025)
his study aims to explore how the integration of Islamic economic literacy and Hulondalo local values shapes financial independence among youth in Gorontalo. Using a qualitative phenomenological approach, the study involved youth from diverse social and educational backgrounds as key informants. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that Islamic economic literacy has not been fully internalized among Gorontalo’s youth; however, Hulondalo values such as tuwoto (hard work), mo’opo (frugality), modutu (mutual cooperation), and tulodo (exemplary conduct) serve as strong foundations for positive financial behavior. The integration between Islamic financial principles and local cultural values strengthens responsibility, independence, and moral awareness in personal financial management. This study highlights that local wisdom can effectively reinforce Islamic economic literacy in promoting financial independence among Gorontalo youth.